PERANAN KEPEMIMPINAN CAMAT DALAM MEWUJUDKAN EFEKTIVITAS PELAYANAN PUBLIK DI DISTRIK TIOMNERI KABUPATEN LANNY JAYA PROPINSI PAPUA - YIGIBALOM, PAIS; Posumah, Johnny Hanny; Rompas, Wilson Yappy (JURNAL ADMINISTRASI PUBLIK, 2017)
ABSTRACTThe purpose of this research is to know the role of the leadership of the head of thepublic service effectiveness in realizing in the district Tiomneri Lanny Jaya province of Papua.Research using qualitative methods. The informant as much research 5 persons i.e.4people Tiomneri District Clerk and 1 non-public figures. Data collection with interviewtechniques; While data analysis using interactive model analysis techniques from Miles and Hubernann.Based on the results of the research can be drawn the conclusion: (1) the role of the leadership of the headof the public service effectiveness in realizing in the district Tiomneri has done well but has not been fullestviews of a role in planning the activities of the public service, a role in the construction of the implementationof the activities of the public service, a part in the supervision of the implementation of the public service,and role in the evaluation of the implementation of the activities of the public service. (2) the effectivenessof the public service in the Office of the District of Tiomneri is already good but haven't been fullest views interms of efficient service,responsifitas service, service transparency, equality and justice get service, andaccountability services.Based on the conclusions suggested: (1) the role of the head of leadership in the public service in the Districtof Tiomneri needs to be improved both in terms of planning activities, in the construction of theimplementation activities, in supervisory activities, as well as in the evaluation of the implementation of theactivities of the public service. For that head of the need to enhance the capabilities of hissubordinate officers in the lead in the preparation of the planning, implementation, supervision, andevaluation of the implementation of the activities of the public service. (2) the effectiveness of the publicservices in the district Tiomneri of peru increased in both in terms of the efficiency ofthe service, responsifitas service, Ministry of Justice, Ministry ofthe transparency, accountability and service. For that Head needs to improve the quality of its leadership sothat the employees can carry out his duties as well as possible with the public service.Keywords: head of leadership, effectiveness of public services.